(untitled) - Ivins, Molly (New York, 2003)
For years, bestselling commentator Molly Ivins has been sounding the alarm about George W. Bush. Now, in their second book on our current White House occupany, Molly Ivins and Lou Dubose take the wire brush to the Bush presidency and show how he has applied the same flawed strategies he used in governing Texas to running the largest superpower in the world.
Keywords: English language,Ngôn ngữ Anh; Study and teaching,Học và dạy